2003
DOI: 10.1095/biolreprod.102.008672
|View full text |Cite
|
Sign up to set email alerts
|

DNA Double-Strand Breaks and γ-H2AX Signaling in the Testis1

Abstract: Within minutes of the induction of DNA double-strand breaks in somatic cells, histone H2AX becomes phosphorylated at serine 139 and forms gamma-H2AX foci at the sites of damage. These foci then play a role in recruiting DNA repair and damage-response factors and changing chromatin structure to accurately repair the damaged DNA. These gamma-H2AX foci appear in response to irradiation and genotoxic stress and during V(D)J recombination and meiotic recombination. Independent of irradiation, gamma-H2AX occurs in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
150
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(170 citation statements)
references
References 45 publications
20
150
0
Order By: Relevance
“…Phoshorylated γH2AX‐histone protein is associated with both DNA double strand breaks and sex vesicle formation in the testis (Hamer et al ., 2003). It is expressed in a subset of the diploid spermatogonia, step 11–14 haploid spermatids and tetraploid spermatocytes (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Phoshorylated γH2AX‐histone protein is associated with both DNA double strand breaks and sex vesicle formation in the testis (Hamer et al ., 2003). It is expressed in a subset of the diploid spermatogonia, step 11–14 haploid spermatids and tetraploid spermatocytes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is expressed in a subset of the diploid spermatogonia, step 11–14 haploid spermatids and tetraploid spermatocytes (Fig. 5A) (Hamer et al ., 2003; Meyer‐Ficca et al ., 2005). FxCycle DNA stain was used to detect the DNA content of the cells in the γH2AX‐S139 assay.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we chose S139‐phophorylated γH2AX (pH2AX) as a proxy for DNA damage and meiotic DSB repair. When spermatocytes accumulate DNA damage due to ionizing radiation or chemotherapeutics, distinct foci of positive pH2AX signal can be observed in the nuclei outside the sex body (Hamer et al ., 2003) and the levels of pH2AX can be used to assess the faithfulness of the meiotic recombination. There were no alterations in the pH2AX staining pattern in the E2F1 −/− ‐testis at P40 compared with E2F1 +/+ , which indicated that increased DNA damage was not the source of the spermatocyte apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylated H2AX (g-H2AX) foci are markers of DNA double strand breaks [Rogakou et al, 1998]. g-H2AX content in testicular cells is heterogeneous, higher than in cells from other organs and increases after irradiation [Hamer et al, 2003;Ahmed et al, 2007Ahmed et al, , 2010aBlanco-Rodriguez, 2009;Paris et al, 2011]. The presence of H2AX has been documented in human [Gatewood et al, 1990] and in mouse [Meyer-Ficca et al, 2009] sperm chromatin.…”
Section: Discussionmentioning
confidence: 99%